Neoplasia in 125 donkeys (Equus asinus): literature review and a survey of five veterinary schools in the United States and Canada. (November 2016) - Davis, Corrine R.; Valentine, Beth A.; Gordon, Emma; McDonough, Sean P.; Schaffer, Paula A.; Allen, Andrew L.; Pesavento, Patricia
A diagnosis of neoplasia was noted in 125 of 357 donkeys (35%) in our review of medical records from 5 veterinary schools in the United States and Canada. Equine sarcoid was the most common tumor in our study, accounting for 72% of all tumors and 82% of cutaneous tumors. Soft-tissue sarcomas were the second most common skin tumors. All other types of neoplasia were rare. Important differences in the occurrence of neoplasia in donkeys compared to horses included the rarity or absence of squamous cell carcinoma in any organ system and gray horse melanoma. Lymphosarcoma, the most common malignant tumor in horses, appears to be very rare in donkeys. We report several tumors in donkeys including melanocytoma, peripheral nerve sheath tumor, and gastrointestinal stromal tumor. Our data demonstrate commonalities as well as differences in neoplastic diseases of donkeys and horses. Understanding differences in carcinogenesis among these 2 closely related species can inform researchers pursuing pathogenic mechanisms of equine disease and inform veterinary diagnosticians regarding tumor prevalence.